2018
DOI: 10.4149/av_2018_401
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genetic diversity of porcine bocavirus in piglets in China

Abstract: Porcine bocavirus (PBoV) is a recently discovered, non-enveloped and single-stranded DNA virus that can infect pigs. In order to understand PBoV infection and its genetic characterization in piglets in Xinjiang China, PBoV was detected by PCR in 156 clinical samples from 1-month-old piglets. PBoV was detected in 9 clinical samples, with a prevalence rate of 5.77% (9/156). Then nonstructural protein NS1 gene was amplified, sequenced and used for phylogenetic analysis. The results showed that the prevalence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In China, the prevalence rate of PBoV in stool samples of piglets was found to be 12.59% (Cheng et al 2010). Similarly, the prevalence rate of bocaviruses in clinical samples from one-month-old piglets was reported to be 5.77% (9/156) (Meng et al 2018). Another study reported that the prevalence rate of PBoV was 18.1% (84/463) (Zhou et al 2018).…”
Section: Discovery and Epidemiology Of Pbovmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, the prevalence rate of PBoV in stool samples of piglets was found to be 12.59% (Cheng et al 2010). Similarly, the prevalence rate of bocaviruses in clinical samples from one-month-old piglets was reported to be 5.77% (9/156) (Meng et al 2018). Another study reported that the prevalence rate of PBoV was 18.1% (84/463) (Zhou et al 2018).…”
Section: Discovery and Epidemiology Of Pbovmentioning
confidence: 99%
“…Lymph nodes, spleen, and tonsil have the highest detection rate suggesting that these organs are the sites of active replication and the pathogenesis of PBoV infections may involve the lymphoid tissues and gastrointestinal tract (Jacob et al 2018). Besides tissues, bocavirus has been detected from the saliva (Choi et al 2014) and serum (Csagola et al 2012;Choi et al 2014;Meng et al 2018). In brief, bocavirus has been isolated from different tissues of the pig, but it is still not clear which cells in pigs are responsible for its multiplication and dissemination throughout the body.…”
Section: Pathogenesis Of Pbovmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers of Viruses including PEDV, PDCoV, TGEV, RV, SADS-CoV, PTV, PKV, PBV, PBoV, SaV, PSV, NOV and PCV4 have been found from the literature [4][5][6][7][8][9][10][11][12][13]. 5 prime pairs were designed based on the reference sequence of the PCL virus 21 and 22 strain determined in the United States and the PCL virus GX14, GX15 and GX19 detected in China (Table 1).…”
Section: Pcr Detectionmentioning
confidence: 99%
“…Newborn piglets are highly vulnerable to some enterovirus infections, causing severe diarrhea, enteritis and vomiting. Enteric pig viruses include porcine epidemic diarrhoea virus (PEDV), porcine delta coronavirus (PDCoV), porcine transmissible gastroenteritis virus (TGEV), swine acute diarrhoea syndrome coronavirus (SADS-CoV), porcine sapelovirus (PSV), porcine rotavirus (RV), porcine picobirnavirus (PBV), porcine circovirus 4 (PCV4), porcine teschovirus (PTV), porcine kobuvirus(PKV), porcine bocavirus(PBoV), porcine sapovirus (SaV), porcine circovirus-like virus(PCL virus) and porcine norovirus (NoV), was detected at porcine farms in China [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%